The Study of Oxygen Production System with Multi-Blades Wind Turbine Using the Energy Storage in Compressed Air - พลาศัย, วสันต์; พรหมเมศร์, พลากร (Princess of Naradhiwas University Journal, 2018)
This study is working on compressed air systems for multiple wind turbines at low wind speeds for aquaculture pond to find the wind speed in the appropriate area for the compressed air system, flow rate of air inside and determine the pressure of the air inside the compressed air tank while compressed. In the compressed air system, compressed air is compressed from the compressor to the wind turbine sprocket. The compressed air test consists of (1) Pressure Transmitter to record the pressure in the air tank. (2) Air Flow Transmitter to monitor the flow inside the pipe. (3) Anemometer to measure wind speed while testing. (4) Data Logger to record each time period. The results of the actual wind speed measurements in the area were 3 m/s, maximum internal flow rate were 3 m3/s and the pressure within the tank was 5 bar. Which shows that the results of the experiments are suitable for the production of oxygen in multi-turbine aquaculture pond. This is another option of energy conservation that can save energy from the traditional way of producing oxygenby using electric motors. Oxygen production system using multi-blade wind turbine to drive compressor for compressed air is a model for practical application to reduce the electricity bill each month and also to bring the knowledge and principles to the community or organizations concerned.